Business Idea Blueprint of Thermassage : Lilstech Enterprise / Nur Haliza Md Alimuddin - Md Alimuddin, Nur Haliza (2020)
Occupational fatigue has been a problem due to long day activities and working among the employees and students. The exhaustion from working in front of a screen or doing lots of physical activities may lead to body muscle pain and stress. LilsTech Enterprise comes up with a new product of Thermassage, which is a portable thermal massage device. This product applies the real Shiatsu and percussion massaging techniques with additional thermal therapy functions which using a Peltier effect technology. This product is mainly targeted to solve the occupational fatigue problem among working employees and students. The distinctive additional value in Thermassage is at advantage from the competitors in the massage equipment market. The pricing strategy and annual projection of this product is estimated to bring profitability towards the business. In addition, this business is assisted by experienced management team members in technology and financial sector to ensure the company can achieve its objectives and goals successfully.